Advanced spatial data management in distributed and real-time environments - Zhang, Jun (2010)
This is a Supplementary Equipment Project (SEP) to provide extra equipment support for the ongoing RG 9/05 Project. As we proceeded with the RG9/05 Project using the equipments initially budgeted, we found that we are running very short on the storage space in our servers. This is mainly due to the fact that we have sensors continuously running, generating huge amount of data all the time. These data has to be stored in our servers to enable further processing. With the very limited storage in our current servers, we cannot perform experiments with real large datasets. We subsequently proposed this Supplementary Equipment Project (SEP). The successful implementation of this SEP has nicely solved the equipment problem and significantly contributed to the success of the RG 9/05 Project.